(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Samoilova M.B. Keywords: genre, persuasion, strategy, tactic, text, discourse. Persuasion in A.P. Chekhov’s belletristic works is represented in the article through speech genres theory and psycholinguistics. This approach allows tracing the links between strategic task of persuasion, its tactical realization, the author’s choice of language material and psychological phenomena of speech activity - stimulus, motive, aim and axiological orientation. The specific feature of the author’s realization of the genre ‘persuasion’ in A.P. Chekhov’s prose is the use of demonstrative tactics, which include texts of different genres: folkloric, literary, conversational. They are the result of the addresser’s creative fantasy, effecting the emotions of the addressee and the reader.